Progressive collapse fragility of substandard and earthquake-resistant precast RC buildings. (15th January 2023) - Scalvenzi, Martina; Ravasini, Simone; Brunesi, Emanuele; Parisi, Fulvio
Highlights: Performance-based robustness assessment of precast RC frame buildings under column loss via nonlinear time history analyses. Computational procedure based on nonlinear capacity modelling of frame members and beam-column connections. Investigation of different beam-column connections representative of low-rise European commercial buildings. Progressive collapse fragility models for precast buildings designed for earthquake resistance with or without horizontal ties in beams. Comparison between mean-centred (deterministic) and probabilistic robustness assessments. Abstract: Several natural and man-made disasters have highlighted that precast reinforced concrete (RC) buildings often have insufficient levels of structural robustness, which is the last line of defence under extreme events. Even though robustness studies were originated by the progressive collapse of the Ronan Point precast RC building in 1968, such a structural feature of disaster resilience has been partially investigated in case of precast RC buildings to date. In this study, a precast RC frame structure representative of low-rise commercial buildings is analysed under different column loss scenarios, which can produce the partial or total collapse of the structural system. Two building classes are considered, namely, buildings designed only to gravity loads and buildings designed for earthquake resistance. Structural robustness is probabilistically assessed through a fragility analysis procedure, using three-dimensional fibre-based finite element models with nonlinear links simulating connections, large-displacement incremental dynamic analysis, and multiple performance limit states for damage assessment. The output of the study is threefold: (i) a detailed assessment of the effects of column loss on precast RC frame buildings, quantifying the major role of structural detailing and beam-column connections; (ii) a fragility-informed evaluation of beneficial effects of seismic detailing on structural robustness, which can drive designers in retrofitting of existing precast RC buildings and decision-makers towards prioritization-related issues; and (iii) the generation of typological fragility curves for progressive collapse risk assessment in both single- and multi-hazard environments. Progressive collapse fragility curves can be convolved with more classical fragility models describing the failure of single components (under, e.g., flow-type landslide impact, vehicle collision or blast) and hazard, to assess systemic structural risk.